Water-based flame-retardant aerogel coating as well as preparation method and application thereof
By using a variety of flame retardant composites and hollow glass microbead fillers in aqueous aerogel insulation coatings, the problem of poor flame retardant effect at high temperatures is solved, and the high flame retardant performance and thermal insulation effect at low thickness are achieved.
Patent Information
- Application Number
- CN202510004463.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-02
- Publication Date
- 2025-04-11
AI Technical Summary
It is difficult for existing aqueous aerogel insulation coatings to achieve excellent flame retardant effects at high temperatures, resulting in limited application in scenarios with high flame retardant requirements.
The composite design of a variety of flame retardants is adopted, combined with hollow glass microbeads as auxiliary functional fillers, to enhance the flame retardant performance of the paint and ensure that the paint can still meet high flame retardant standards under low thickness through specific formulations.
The UL94 V0-grade flame retardant performance of the coating at a thickness of 0.5mm is achieved, while maintaining a low thermal conductivity, ensuring both flame retardant and thermal insulation properties.
Smart Images

Figure BDA0005226458440000081 
Figure BDA0005226458440000091 
Figure BDA0005226458440000092
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of coatings, and in particular to a water-based flame-retardant gas gel coating and a preparation method and application thereof. Background Art
[0002] Aerogel material has the lowest thermal conductivity among all known solid materials in the world. If aerogel is used as a thermal insulation material, its thermal insulation performance will be better than other materials on the market. Aerogel has a porous three-dimensional structure with a porosity of more than 95%. The diameter of the pores is nanometer-level. Since the pore size of aerogel is 20-50nm, which is smaller than the mean free path of air molecules, the free flow of air is restricted. The porosity of more than 95% can achieve a vacuum-like thermal insulation effect, and more than 95% of the pores also form a radiation surface and a reflection surface for heat, which greatly restricts the thermal radiation of heat. Therefore, aerogel has excellent thermal insulation performance.
[0003] However, the water-based aerogel thermal insulation coatings on the market basically cannot achieve excellent flame retardant effects, especially when the temperature of silica aerogel exceeds 650°C. The high temperature will destroy the connection structure of the silica aerogel skeleton, causing the support structure to collapse and the aerogel pores to collapse. As a result, the various properties of the silica aerogel will decrease, the thermal conductivity will increase, and the thermal insulation performance will be greatly reduced. Therefore, most aerogels are difficult to use in some scenarios with high flame retardant requirements, such as high-power heating equipment, gallium nitride charging heads, etc. Therefore, it is urgent to develop a water-based aerogel thermal insulation coating with excellent flame retardant properties for use in the field of thermal management to expand the application of aerogel in high flame retardant environments. Summary of the invention
[0004] In view of the defects in the prior art, the present invention provides a water-based fire-retardant gel coating and a preparation method and application thereof.
[0005] The present invention provides a water-based flame-retardant gas gel coating, which comprises the following components by weight: 25-35 parts of water-based resin emulsion, such as 25, 28, 30, 32, and 35 parts; 5-10 parts of aerogel powder, such as 5, 6, 7, 8, 9, and 10 parts; 30-50 parts of flame retardant, such as 30, 35, 40, 45, and 50 parts; 2-8 parts of filler, such as 2, 3, 4, 5, 6, 7, and 8 parts; 2-10 parts of hollow glass microspheres, such as 2, 3, 4, 5, 6, 7, 8, 9, and 10 parts; 0.2 -1 part, such as 0.2, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1 part; water 10-15 parts, such as 10, 11, 12, 13, 14, 15 parts; defoamer 1-3 parts, such as 1, 2, 3 parts; emulsifier 0.5-1, such as 0.5, 0.6, 0.7, 0.8, 0.9, 1 part; stabilizer 1-2 parts, such as 1, 1.2, 1.4, 1.6, 1.8, 2 parts; leveling agent 0.1-0.5 parts, such as 0.1, 0.2, 0.3, 0.4, 0.5 parts.
[0006] The present invention uses a variety of flame retardants to jointly enhance the flame retardant properties of the material, while ensuring the thermal insulation function of the coating. Among them, the inorganic material flame retardant has the characteristic of low thermal conductivity, which has little effect on the thermal conductivity of the coating and will not greatly affect the thermal insulation performance of the coating. It can also enhance the flame retardant properties of the coating. The thermal conductivity of the phosphorus-nitrogen flame retardant is lower than that of the metal oxide flame retardant, and has little effect on the thermal conductivity of the coating. When adding the compound flame retardant, hollow glass microspheres are used as auxiliary functional fillers. Hollow glass microspheres can be used as secondary binders for coatings under high temperature conditions, further enhancing the flame retardant properties of the coating. When the combustion temperature reaches the melting point of the hollow glass microspheres, the hollow glass microspheres melt into liquid glass and become high-temperature binders, which can prevent dripping and improve the flame retardant properties. Due to its low thermal conductivity and good thermal insulation properties, it can also maintain the thermal insulation properties of the coating. In addition, the mutual cooperation between the components enables the coating to meet the UL94-V0 standard for a thickness of about 0.5 mm without losing the thermal insulation effect. The present invention uses a specific formula and a compound design of a flame retardant, and compared to the product in the prior art that needs to reach a thickness of 2 mm to achieve a flame retardant property of V-0, the obtained coating can achieve a flame retardant property of V-0 when the thickness reaches about 0.5 mm.
[0007] The invention can make the coating thinner through formula design, and can be made into a thin film product with substrates such as PET and PI. It is suitable for automated die-cutting processes and has low processing costs. It can be widely used in industries such as consumer electronics and new energy that have flame retardancy and thermal management requirements in narrow spaces.
[0008] The invention provides a water-based flame-retardant gel coating with good adhesion to plastic substrates such as cement, PET, PI, ABS, PVC and the like and metal substrates such as aluminum and copper through formula design. That is, the flame-retardant gel coating can be used as a plastic film substrate such as PET, PI, PVC, PS and the like, and coated into a coil by a scraper coating line to form a flame-retardant gel film, or can be directly attached to metal substrates such as copper and aluminum and plastic substrates such as ABS, PC, PET and the like by spraying or brushing.
[0009] Furthermore, the water-based resin emulsion is at least one of styrene-acrylic emulsion, silicone-acrylic emulsion, pure acrylic emulsion, and polyurethane dispersion emulsion.
[0010] Furthermore, the wetting dispersant is one or a combination of ionic dispersants, polycarboxylate dispersants, and polymer dispersants, preferably one or more of Nopco 5040 dispersant, BYK-190 dispersant, Shenzhu SN1729 dispersant, Huaxia 5320 dispersant, and YCK2590 dispersant.
[0011] Furthermore, the aerogel powder is at least one of silica aerogel powder, alumina aerogel powder, zirconia aerogel powder or graphene aerogel.
[0012] Furthermore, the flame retardant is a combination of phosphorus-nitrogen flame retardant, ceramic flame retardant and inorganic flame retardant. The flame retardant compounding mass ratio is inorganic flame retardant:phosphorus-nitrogen flame retardant:ceramic flame retardant=8:(20-28):(3-8).
[0013] Furthermore, the filler is one or more of talc, light calcium carbonate, heavy calcium carbonate, precipitated barium sulfate, wollastonite, and sericite.
[0014] Furthermore, the defoamer is any one of an organosilicon defoamer, a silicon-free defoamer, a polyether defoamer, an acetylene alcohol defoamer, and a mineral oil defoamer.
[0015] Furthermore, the emulsifier is any one or more of OP-10 and Tween 20, the stabilizer is a silicate stabilizer, and the leveling agent is a modified silane leveling agent.
[0016] Furthermore, the D90 particle size of the hollow glass microspheres is 10-30 μm. If the particle size is too small, the specific surface area will increase, the interaction force between the particles will be enhanced, and agglomeration will easily occur, affecting the dispersibility and storage stability of the coating. Filler particles that are too small will also adhere to each other due to static electricity during the coating process to form lumps, resulting in inconvenience in construction. Fillers that are too large in particle size will cause uneven dispersion of pigments in the coating, affecting the color uniformity and consistency of the coating, and easily causing uneven surfaces, affecting the flatness of the coating. The present invention selects hollow glass microspheres with a particle size D90 within a specific range, so that the prepared coating can take into account the advantages of appearance, stability, and construction performance.
[0017] The present invention also provides a method for preparing the aerogel coating, comprising the following steps:
[0018] S1. Weigh each component by weight, add water to a dispersion tank, add a wetting dispersant and an emulsifier in sequence under stirring, and disperse uniformly to obtain a mixture 1;
[0019] S2. The aqueous resin emulsion is added to the mixture 1 of step S1 for the first dispersion until the dispersion is uniform, and the phosphorus nitrogen (liquid) flame retardant and the inorganic (liquid) flame retardant are added under stirring for the second dispersion until the dispersion is uniform to obtain a mixture 2;
[0020] S3. The aerogel powder is added to the mixture 2 in step S2 and dispersed evenly to obtain a mixture 3 under stirring;
[0021] S4. Add the ceramic (powder) flame retardant to the mixture 3 of step S3 under stirring and disperse it for the first time until it is evenly dispersed, add the filler under stirring and disperse it for the second time until it is evenly dispersed; continue to add the hollow glass microspheres under stirring and disperse them for the third time until they are evenly dispersed to obtain a mixture 4;
[0022] S5. The stabilizer and the leveling agent are added to the mixture 4 of step S4 and dispersed under stirring until uniformly dispersed to obtain a mixture 5;
[0023] S6. Add the defoaming agent to the mixture 5 of step S5 under stirring to disperse it, then reduce the rotation speed to perform mechanical defoaming until there are no obvious bubbles, thus obtaining a water-based flame-retardant gas gel coating, which can then be ground to obtain a viscous liquid water-based flame-retardant gas gel coating.
[0024] In the system of the present invention, the three flame retardants have a synergistic effect and simultaneously play a role in improving the flame retardancy of the bonding resin, the inert flame retardancy and the ceramic reaction flame retardancy. In particular, the addition of the ceramic powder flame retardant can make the material react when combustion occurs, forming a ceramic layer on the surface, blocking the flame from continuing to penetrate deeper, and significantly improving the flame retardancy of the material.
[0025] Further, the speed of dispersion in step S1 is 500-800r / min, and the time is 12-20min; the first dispersion in step S2 is dispersed at 500-800r / min for 12-20min, and the second dispersion is dispersed at 800-1200r / min for 25-35min; the speed of dispersion in step S3 is 1200-1500r / min, and the time is 25-35min; the first dispersion in step S4 is dispersed at 1200-1500r / min for 25-35min, and the second dispersion is dispersed at 1200- The dispersion is carried out at 1500 r / min for 10-15 min, at 1000-1200 r / min for 30 min, and the third dispersion is carried out at 1000-1200 r / min for 25-35 min; the dispersion in step S5 is carried out at 1000-1200 r / min for 15-20 min; the dispersion in step S6 is carried out at 1000-1200 r / min for 25-35 min; the mechanical defoaming is carried out at 800-1000 r / min for 1-2 h, and the grinding is carried out in a three-roll mill, and the fineness reaches 30-50 μm.
[0026] The present invention also provides application of the aerogel coating in consumer electronics, new energy and energy storage.
[0027] In summary, compared with the prior art, the present invention achieves the following technical effects:
[0028] (1) The water-based flame-retardant gas gel coating provided by the present invention has high flame retardant properties, and its flame retardant properties meet the UL94 V0 and VTM-0 standards at a low thickness of 0.5 mm;
[0029] (2) The water-based flame-retardant gas gel coating provided by the present invention has a low thermal conductivity coefficient and can take into account both flame retardancy and heat insulation properties;
[0030] (3) The water-based flame-retardant gel coating provided by the present invention has a simple preparation process, is free of organic solvents, is green and environmentally friendly, has low cost, and uses water as a diluent to reduce VOS emissions;
[0031] (4) The water-based flame-retardant gas gel coating provided by the present invention has a light and thin thickness, can achieve high flame retardant performance at a low thickness, can be made into a thin film product with substrates such as PET and PI, is suitable for automated die-cutting processes, and has low processing costs;
[0032] (5) The water-based flame-retardant gas gel coating provided by the present invention has low equipment requirements and has good adhesion on plastic substrates such as cement, PET, PI, ABS, PVC and hardware substrates such as aluminum and copper. DETAILED DESCRIPTION
[0033] In order to enable those skilled in the art to better understand the solutions of the present invention, the technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only embodiments of a part of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.
[0034] Example
[0035] The present invention is further described below in conjunction with specific examples and comparative examples. The following specific examples are all preferred embodiments of the present invention, but the embodiments of the present invention are not limited to the following examples, and are particularly not limited to the types of the various component raw materials used in the following specific examples.
[0036] 1. The sources of raw materials for the embodiments and comparative examples are as follows:
[0037] Unless otherwise specified, the raw materials used in the embodiments of the present invention are commercially available.
[0038] The preparation method of the water-based flame-retardant gas gel coating of the embodiment of the present invention comprises the following steps:
[0039] S1. Weigh each component by weight, add water to a dispersion tank, add a wetting dispersant and an emulsifier in sequence under stirring, and disperse uniformly to obtain a mixture 1;
[0040] S2. The aqueous resin emulsion is added to the mixture 1 of step S1 for the first dispersion until the dispersion is uniform, and the phosphorus nitrogen (liquid) flame retardant and the inorganic (liquid) flame retardant are added under stirring for the second dispersion until the dispersion is uniform to obtain a mixture 2;
[0041] S3. The aerogel powder is added to the mixture 2 in step S2 and dispersed evenly to obtain a mixture 3 under stirring;
[0042] S4. Add the ceramic (powder) flame retardant to the mixture 3 of step S3 under stirring and disperse it for the first time until it is evenly dispersed, add the filler under stirring and disperse it for the second time until it is evenly dispersed; continue to add the hollow glass microspheres under stirring and disperse them for the third time until they are evenly dispersed to obtain a mixture 4;
[0043] S5. The stabilizer and the leveling agent are added to the mixture 4 of step S4 and dispersed under stirring until uniformly dispersed to obtain a mixture 5;
[0044] S6. Add the defoaming agent to the mixture 5 of step S5 under stirring and disperse it, then reduce the speed for mechanical defoaming until there are no obvious bubbles, and then grind it to obtain a viscous liquid water-based flame-retardant gel coating;
[0045] The speed of dispersion in step S1 is 500-800 r / min, and the time is 12-20 min; the first dispersion in step S2 is at 500-800 r / min for 12-20 min, and the second dispersion is at 800-1200 r / min for 25-35 min; the speed of dispersion in step S3 is 1200-1500 r / min, and the time is 25-35 min; the first dispersion in step S4 is at 1200-1500 r / min for 25-35 min, and the second dispersion is at 1200-1 The dispersion is carried out at 500 r / min for 10-15 min, at 1000-1200 r / min for 30 min, and the third dispersion is carried out at 1000-1200 r / min for 25-35 min; the dispersion in step S5 is carried out at 1000-1200 r / min for 15-20 min; the dispersion in step S6 is carried out at 1000-1200 r / min for 25-35 min; the mechanical defoaming is carried out at 800-1000 r / min for 1-2 h; the grinding is carried out in a three-roll mill, and the fineness reaches 30-50 μm.
[0046] 2. Various performance test methods
[0047] The coating prepared in the example was evenly coated on a 0.015 mm PET film substrate and dried at room temperature for more than 7 days to obtain a dried coating. The coating dry film thickness was maintained at 0.5±0.05 mm, and the coating dry film performance was tested.
[0048] (1) Coating appearance: Visual inspection: the coating surface should be flat without obvious bumps and waves. Observe whether the appearance of the dry coating surface is normal.
[0049] (2) Surface drying time: Observe the surface drying time of the coating according to the provisions of GB / T 1728-2020 "Determination of Drying Time of Paint Film and Putty Film".
[0050] (3) Thermal conductivity: ISO 22007-2-2008 Plastics. Determination of thermal conductivity and thermal diffusivity.
[0051] (4) Thermal insulation temperature difference: Use a digital constant temperature heating table and a multi-channel temperature controller to test the thermal insulation temperature difference. Place sensor 1 on the hot surface (source) close to the back of the sample, and sensor 2 on the front of the sample. In a relatively closed, windless environment, start the test after reaching the set temperature, maintain the set temperature and continue heating for 30 minutes, record the temperature of sensor 1 and sensor 2, and calculate the temperature difference.
[0052] (5) Flame retardant properties: tested using a horizontal vertical flame tester in accordance with the UL-94-2023 standard.
[0053] (6) Thickness: Use a thickness gauge to test in accordance with GB / T 6627-2001 "Mechanical measurement of thickness of plastic films and sheets" (the thickness is the thickness of the coating plus the substrate).
[0054] Example 1
[0055] The raw materials used in Example 1 are as follows:
[0056]
[0057]
[0058] Example 2
[0059] The raw materials used in Example 2 are as follows:
[0060]
[0061] Example 3
[0062] The raw materials used in Example 3 are as follows:
[0063]
[0064]
[0065] Example 4
[0066] The raw materials used in Example 4 are as follows:
[0067]
[0068]
[0069] Example 5
[0070] The raw materials used in Example 5 are as follows:
[0071]
[0072] Comparative Example 1
[0073] The raw materials used in Comparative Example 1 are as follows:
[0074]
[0075]
[0076] Table 1 Performance test results of the embodiment
[0077]
[0078] Examples 1-5 all introduce a specific flame retardant combination and hollow glass microspheres at the same time, and aerogel coatings are made through a special formula. The finally prepared water-based flame-retardant aerogel coatings can achieve high thermal insulation effects while maintaining good flame retardant properties, wherein the thermal conductivity is 0.052W / (m·K) or less, the thermal insulation temperature difference at 120°C is 29°C or more, and the flame retardancy reaches UL-94V1 powder level or above. At the same time, it has the characteristics of quick drying, the surface drying time is less than 2h, and it is light and thin, with a thickness of less than 0.55mm, and can also ensure a smooth appearance.
[0079] Compared with Example 4, Comparative Example 1 did not add three specific flame retardants for compounding, so that the flame retardant performance of the coating was significantly reduced.
[0080] Based on the test data of thermal conductivity, appearance, surface drying time, thickness, thermal insulation performance and flame retardant performance in Table 1, the water-based flame retardant gas gel coating prepared by Examples 1-5 has obvious advantages in flame retardancy and thermal insulation, and can effectively meet the high standards of customers and the market.
[0081] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A water-based flame-retardant gel coating, characterized in that: By weight, it includes the following components:
2. The aerogel coating according to claim 1, characterized in that: The water-based resin emulsion is at least one of styrene-acrylic emulsion, silicone-acrylic emulsion, pure acrylic emulsion and polyurethane dispersion emulsion.
3. The aerogel coating according to claim 1, characterized in that: The wetting dispersant is one or a combination of ionic dispersants, polycarboxylate dispersants and polymer dispersants.
4. The aerogel coating according to claim 1, characterized in that: The aerogel powder is at least one of silicon dioxide aerogel powder, aluminum oxide aerogel powder, zirconium oxide aerogel powder or graphene aerogel.
5. The aerogel coating according to claim 1, characterized in that: The flame retardant is a combination of a phosphorus-nitrogen flame retardant, a ceramic flame retardant and an inorganic flame retardant.
6. The aerogel coating according to claim 1, characterized in that: The filler is one or more of talc, light calcium carbonate, heavy calcium carbonate, precipitated barium sulfate, wollastonite and sericite.
7. The aerogel coating according to claim 1, characterized in that: The defoamer is at least one of an organosilicon defoamer, a silicon-free defoamer, a polyether defoamer, an acetylene alcohol defoamer, and a mineral oil defoamer.
8. The aerogel coating according to claim 1, characterized in that: The D90 particle size of the hollow glass microspheres is 10-30 μm.
9. The method for preparing the aerogel coating according to any one of claims 1 to 8, characterized in that: The steps include: S1. Weigh each component by weight, add water to a dispersion tank, add a wetting dispersant and an emulsifier in sequence under stirring, and disperse uniformly to obtain a mixture 1; S2. The aqueous resin emulsion is added to the mixture 1 of step S1 for the first dispersion until the dispersion is uniform, and the phosphorus nitrogen flame retardant and the inorganic flame retardant are added under stirring for the second dispersion until the dispersion is uniform to obtain a mixture 2; S3. The aerogel powder is added to the mixture 2 in step S2 and dispersed evenly to obtain a mixture 3 under stirring; S4. Add the ceramic flame retardant to the mixture 3 of step S3 under stirring and disperse it for the first time until it is evenly dispersed, add the filler under stirring and disperse it for the second time until it is evenly dispersed; continue to add the hollow glass microspheres under stirring and disperse them for the third time until the mixture is evenly dispersed to obtain a mixture 4; S5. The stabilizer and the leveling agent are added to the mixture 4 of step S4 and dispersed under stirring until uniformly dispersed to obtain a mixture 5; S6. Add the defoaming agent to the mixture 5 of step S5 under stirring for dispersion, and then reduce the rotation speed for mechanical defoaming until there are no obvious bubbles, thereby obtaining a water-based flame-retardant gas gel coating.
10. Application of the aerogel coating according to any one of claims 1 to 8 in consumer electronics, new energy and energy storage.
Citation Information
Cited By
Coal gangue-based alumina aerogel thermal insulation coating and preparation method thereof
CN122146122A